Shawaragad Gadle : yeakuri gadlat balabet, 1878-1943 : yehiywot tarik - Shibashi Lama. (Addis Ababa : Kifle markos Gagle, 2007)
A biography of the late Shawaragad Gadle, an Ethiopian patriot and nationalist.
Includes bibliographical references (pages 218-221) and index.
In Amharic.